Exploring the Positive Impact of Magnesium on Cardiovascular Diseases: A Comprehensive Review - Madyniak, Katarzyna; Żak, Katarzyna; Jucha, Hubert; Kluz, Agnieszka; Pliszka, Aleksandra; Mazur, Michał; Jarych, Weronika; Zukierski, Krystian; Michalak, Katarzyna (Quality in Sport, 2025)
Magnesium plays a critical role in cardiovascular health, being essential for various biochemical processes and maintaining physiological balance. Deficiency in magnesium is linked to conditions such as arrhythmias, hypertension, coronary artery disease and pregnancy-related disorders like preeclampsia and eclampsia. This study aims to investigate the role of magnesium in these cardiovascular conditions and highlight its therapeutic potential. Aim of the Study: The aim of this study is to comprehensively review the role of magnesium in cardiovascular diseases, including arrhythmias, hypertension, coronary artery disease, preeclampsia and eclampsia, with an emphasis on its physiological mechanisms, therapeutic applications, and potential clinical benefits. Material and Methods: A literature review was conducted using PubMed as the primary database. The search terms included: "magnesium", "cardiovascular diseases", "arrhythmia", "hypertension", "coronary artery disease", "preeclampsia" and "eclampsia". Conclusions: Magnesium deficiency contributes to various cardiovascular conditions, particularly arrhythmias, hypertension, coronary artery disease and pregnancy-related complications. Its therapeutic effects are primarily linked to ionic modulation, vasodilation, and anti-inflammatory properties, emphasizing the importance of magnesium in cardiovascular disease prevention and treatment.